1986
DOI: 10.1016/0014-5793(86)81335-7
|View full text |Cite
|
Sign up to set email alerts
|

The structure of rice storage protein glutelin precursor deduced from cDNA

Abstract: The complete amino acid sequence of rice storage protein glutelin was determined by the sequencing of the corresponding cDNA. The deduced glutelin precursor has a 37 amino acid signal peptide sequence at the NH2 terminus, which is followed by a 269 amino acid acidic subunit (Mr = 32 489) and a 193 amino acid basic subunit (Mr = 19 587). The glutelin precursor sequence is homologous to those of pea legumin and soybean glycinin.(Oriza sativa/ Storage protein Glutelin cDNA Glutelin precursor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…In this analysis, globulin mRNA was detectable by 3 Our analysis showed that the amino acid sequence specified by pOG2 is 70% identical to that of the rice globulin (glutelin) reported by Takaiwa et aL (27) (Fig. 5, right).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…In this analysis, globulin mRNA was detectable by 3 Our analysis showed that the amino acid sequence specified by pOG2 is 70% identical to that of the rice globulin (glutelin) reported by Takaiwa et aL (27) (Fig. 5, right).…”
Section: Resultssupporting
confidence: 74%
“…6B) and the rice globulin (glutelin) (Fig. 6C) The oat globulin sequence is from cDNA clone pOG2, the soybean glycinin sequence is from the Gy2 gene (18), and the rice globulin (glutelin) sequence is from cDNA clone pREE6 1 (27). The sequences were aligned using the Microgenie computer program which inserts gaps to maximize homology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the subunit composition of the 64-kD glutelin is different from those of high molecular mass and that the high-molecular-mass glutelins were polymers of the 130-kD protein. This observation is coincident with the reports that different nucleotide sequences of rice glutelin cDNA were found 8,9) and that the protein is encoded in different gene subfamilies. 10 ,11) The 64-kD glutelin does not polymerize as 130-kD glutelin does to form high-molecular-mass glutelin by intermolecular disulfide bridges in the protein body (PB-II).…”
supporting
confidence: 90%
“…The 5 bp deletion caused a frame-shift of the PLA1 gene. The single-base Glutinous endosperm WX (Os06g0133000) Wang et al (1990) Shortened plastochron PLA1 (Os10g0403000) Miyoshi et al (2004) Shortened plastochron PLA2 (Os01g0907900) Kawakatsu et al (2006) Gibberellin deficiency CPS (Os02g0278700) Sakamoto et al (2004) Gibberellin deficiency KAO (Os06g0110000) Sakamoto et al (2004) Gibberellin deficiency GA3ox2 (Os01g0177400) Itoh et al (2001) Gibberellin insensitivity GID1 (Os05g0407500) Ueguchi-Tanaka et al (2005) Gibberellin insensitivity GID2 (Os02g0580300) Sasaki et al (2003) Glutelin deficiency GluA1 (Os01g0762500) Takaiwa et al (1986) Glutelin deficiency GluA2 (Os10g0400200) Takaiwa et al (1987) Glutelin deficiency GluB4/B5 (Os02g0268300/Os02g0268100) Masumura et al (1989) α-Globulin deficiency α-globulin (Os05g0499100) Shorrosh et al (1992) Chlorophyll b deficiency CAO (Os10g0567400) Morita et al (2005) substitution in pla1-g2 (GAG → GTG) resulted in an amino acid substitution of 407th glutamic acid to valine. The other two short plastochron mutants had DNA lesions in PLA2.…”
Section: Waxy Mutantsmentioning
confidence: 99%